Development and preliminary evaluation of a robotic device for mri-guided needle breast biopsy - Ioannides, Cleanthis; Antoniou, Anastasia; Zinonos, Vasiliki; Damianou, Christakis A. (My University, 2024)
This study concerns the development and evaluation of a simple and ergonomic robotic system for Magnetic Resonance Imaging (MRI)-guided needle breast biopsy with lateral needle approach. The device comprises two piezoelectrically actuated linear motion stages intended to align a needle supporter with the target for manual needle insertion. The device demonstrated submillimeter accuracy and safe operation within a 3 T clinical MRI scanner. In phantom studies, tumor simulators of varying sizes were successfully targeted in both laboratory and MRI settings.
Keywords: accuracy; agar phantom; breast biopsy; MRI-guided; positioning device